Improving watershed management practices in humid regions. Issue 18 (28th June 2017) - Zimale, Fasikaw A.; Tilahun, Seifu A.; Tebebu, Tigist Y.; Guzman, Christian D.; Hoang, Linh; Schneiderman, Elliot M.; Langendoen, Eddy J.; Steenhuis, Tammo S.
Abstract: In many parts of the world, watershed management practices have been extremely effective. However, implementation of soil and water conservation technologies in the humid African highlands, while beneficial in the short term, were remarkably unsuccessful in the long term. Insights from community knowledge perspectives have revealed that alternative methods are needed. Although conservation practices are designed to conserve water in semi‐arid areas, safely draining excess water is needed in humid areas. The objective of this paper is to review current watershed management approaches used in humid regions as exemplified by those used in Ethiopian highlands and then based on these findings propose more effective practices. Although current government sponsored practices primarily protect the hillsides, direct run‐off is generated from areas that become saturated on valley bottoms near rivers and on specific parts of the hillsides with degraded soils (or with highly permeable surface soils) and with perched water tables on slowly permeable horizons at shallow depths. In these areas, direct run‐off is increasing with deforestation and the soil degradation, demanding additional drainage ways that evolve in the form of gullies. Therefore, watershed management interventions for erosion control should prioritize revegetation of degraded areas, increasing sustainable infiltration, and rehabilitating gullies situated at saturated bottomlands.